2011
DOI: 10.3892/ijmm.2011.769
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of statins on diabetic nephropathy in db/db mice

Abstract: Abstract. Recent studies suggest a potential benefit of the lipid-lowering medication in the treatment of chronic kidney disease (CKD) such as diabetic nephropathy. Although statins have been widely used to lower serum cholesterol levels, the effect of these drugs on diabetic nephropathy has not been fully elucidated. In the present study, therefore, we addressed the role of different kinds of statins on diabetic nephropathy in db/db mice. Mice were fed with a standard diet with 0.005% (w/w) of pitavastatin, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the present study, db/db mice, with genetic hyperglycemia akin to adult-onset T2DM as a consequence of an inactive gene mutation affecting leptin receptors, were specifically selected as the T2DM model ( 31 33 ); this model has been widely recognized to be well-established animal model for investigating the association between hyperglycemia, EPC function and wound closure ( 34 ). Wound healing following tissue damage is a sophisticated pathophysiological process which requires comprehensive interactions between cells and a variety of signaling molecules ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, db/db mice, with genetic hyperglycemia akin to adult-onset T2DM as a consequence of an inactive gene mutation affecting leptin receptors, were specifically selected as the T2DM model ( 31 33 ); this model has been widely recognized to be well-established animal model for investigating the association between hyperglycemia, EPC function and wound closure ( 34 ). Wound healing following tissue damage is a sophisticated pathophysiological process which requires comprehensive interactions between cells and a variety of signaling molecules ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several animal experiments demonstrated that statins exerted renal benefits that is independent on the lipid-lowering effect. Rosuvastatin treatment for 8 weeks reduced the excretion of urinary albumin and suppressed glomerular hypertrophy in db/db mice even though blood lipid levels were not altered by drug treatment [ 59 ]. In Apo-E knockout mice, rosuvastatin administration for 20 weeks showed renoprotective effects that are irrelevant to the lipid-lowering effect [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in agreement with these and other studies showing that statins improve renal structure both in type 1 and type 2 experimental diabetes [ 8 , 34 36 ] and also in patients with type 1 diabetes [ 37 ]. The effects of atorvastatin observed in our study do not seem to be agent-specific as other statins, such as simvastatin, pitavastatin and rosuvastatin have also been shown to have some renoprotective actions in experimental models of diabetes [ 8 , 38 ].…”
Section: Discussionmentioning
confidence: 58%